Assessment of sweetpotato farming systems, production constraints and breeding priorities in eastern Tanzania. Issue 2 (2nd April 2016) - Ngailo, Stephan; Shimelis, Hussein A; Sibiya, Julia; Mtunda, Kiddo
Abstract : Sweetpotato is an important food security crop in Tanzania. The crop is grown under diverse farming systems with very low yields. The objective of this study was to assess the present sweetpotato farming systems, farmers' preferences, production constraints and breeding priorities in eastern Tanzania. Participatory rural appraisal was conducted in the Gairo, Kilosa and Kilombero districts of the Morogoro region and Mkuranga district of the Coast region of Tanzania. Primary and secondary data were collected using semi-structured interviews, focus group discussions and field observations. The study showed that more than 94% of the respondents depended on farming for their livelihoods. Main sweetpotato production constraints were Sweetpotato virus disease (SPVD) and pests, drought, unavailability of markets and lack of transport, low prices, inadequate extension services and postharvest losses. Preferred sweetpotato attributes included high yield, high dry matter content, tolerance to diseases and early maturity. Farmers expressed their persuasive needs towards improved extension service delivery, SPVD-tolerant cultivars, and reliable and coordinated market systems for sweetpotatoes.